Pengaruh Kepemimpinan Kepala Tata Usaha Terhadap Peningkatan Profesionalitas Kinerja Staf Madrasah Di Madrasah Tsanawiyah (MTs) - Pujiati, Pujiati; Taqiyuddin, Taqiyuddin; Mukhlisoh, Mukhlisoh (JIEM (Journal of Islamic Education Management), 2024)
The chief school administration has function to handle all of school administration internal or external directly accordance with the jobs description as operative work service in reaching the goals of organization itself includes the staff.Â  The problem that the researcher obtained was a leadership difference of the chief school administration in handling the staff works. In detail, staffs of school administrator MTs Salafiyah Bode Plumbon Cirebon were less in understanding professional work aspects, lack of human resources who have ability and capacity parallel with their professional background, and the chief of school administrator did not provide reward and punishment in their professional work. Based on the explanation above, the goals of this research are: to recognize the duty, function and job description of staff school administration MTs Salafiyah Bode Plumbon Cirebon, to comprehend what factors that develops the professional work of staff MTs Salafiyah Bode Plumbon Cirebon, and to gain the effects of giving reinforcement and motivation from the chief of school administration to the staff MTs Salafiyah Bode Plumbon Cirebon. It stated by E. Mulyasa (2011: 97) that a good leader should be manager, administrator, supervisor, innovator and motivator in order to become competitive. The researcher employed quantitative descriptive method. The data collection was taken from four correspondents by conducting observation, documentation and interview. Those data collections were relevant and suitable with research background and the total correspondents that the researcher used only 4. The research findings based on observation and interview data at MTs Salafiyah Bode Plumbon Cirebon showed that the leadership of the chief school administration towards staff professional work at MTs Salafiyah Bode Plumbon Cirebon there was influence stated by 4 correspondents in amount 19,600 and 10,000 which meant Count Hypothesis (Hc) was accepted and Hypothesis was rejected.Â  Therefore, it could be concluded that this research which is entitled The influence of the chief school administration leadership in enhancing staff professional works at Mts Salafiyah Bode Plumbon had been proved the hypothesis to be valid.Keywords: A Leadership, The chief of school administration and professional workÂ